Significance of thiol/disulphide homeostasis and ischemia modified albumin levels in chronic obstructive pulmonary disease - Eroğlu, Oğuz; Dindar Badem, Nermin; Baccıoğlu, Ayşe; Cömertpay, Ertan; Neşelioğlu, Salim; Erel, Özcan (The European Research Journal, 2019)
Objectives: The severity of inflammation occurring during chronic obstructive pulmonary disease (COPD) is closely associated with oxidative stress. The aim of this study was to investigate the diagnostic value of Thiol/disulphide homeostasis (TDH) and ischemia modified albumin (IMA) levels in evaluating oxidative stress in COPD patients. Methods: This prospective study was performed with COPD patients presenting to the Kırıkkale University Hospital and with healthy volunteers. Subjects’ demographic data (age, sex, body mass index, and smoking status), native thiol (NT), total thiol (TT), disulphide (Ds), IMA levels and Ds/NT, Ds/TT and NT/TT ratios were recorded. Statistical analysis was performed with SPSS 21.0 software. Results: One hundred ninety subjects were enrolled in the study, 141 COPD patients and 49 healthy volunteers. No difference was determined between the patient and control groups in terms of age, sex or body mass index. The antioxidant markers; NT and TT levels and NT/TT ratio were significantly lower in the patient group compared to the control group (p < 0.001, p < 0.001, and p < 0.003, respectively). The oxidant markers; IMA levels and Ds/NT and Ds/TT ratios were significantly higher in the patient group (p = 0.006, p = 0.003, and p = 0.003, respectively). Significant negative correlation was determined between antioxidant and oxidant parameters. Sensitivity values were NT: 87.2%, TT: 83.3%, Ds/NT ratio: 68.1%, Ds/TT ratio: 68.1%, and IMA: 77.8%. Conclusions: TDH was impaired in favor oxidants in COPD patients. TDH parameters and IMA can be used to monitor oxidative stress emerging in COPD.